Minicutting technique and IBA application in vegetative propagation of Schinus terebinthifolia Raddi (Research, Society and Development, 2021)
Vegetative propagation is an alternative for the production of seedlings of native tree species such as Schinus terebinthifolia that presents a high predation rate on its seeds. In order to develop vegetative propagation technology, different concentrations of indolebutyric acid (IBA) were tested in the rooting of apical and intermediate minicuttings of Schinus terebinthifolia. The 2x4 factorial experimental design involved two types of minicuttings (apical and intermediate) and four dosages of the hormone IBA (0, 1000, 2000, and 4000 mg. L-1). The percentages of survival and rooting were evaluated. The intermediate minicuttings (37% and 35%) showed significantly greater survival than the apical cuttings (22% and 9%) respectively at 30 and 60 days, regardless of the IBA concentration. Among the rooting averages at 60 days obtained in the different concentrations of IBA, the treatment of 4000 mg. L-1 generated the highest results (9% for apical and 35% for intermediate). The vegetative propagation by minicuttings of Schinus terebinthifolia demonstrated the viability of intermediate minicuttings with high rooting associated with the highest concentration of IBA.